اُچ شریف کی تاریخ اور اس کے جغرافیائی نقوش کا تحقیقی جائزہ : A research review of the history of Uch Sharif and its geographical footprints (Al-Aasar, 2025)
The land of Uch Sharif has been the land of Sufism and religious scholars and Islamic reformation of the people continued in it and about its history, in Minhaj al-Masalik, whose Persian translation is known as (Chach Nama) and which was compiled before 136 AH, Ach is mentioned as Iskanda, Iskanda. Therefore, it is assumed that in the second century the name of the town was Iskanda instead of Ach. In Tuhfatul-Karam 21, its name is written as Ashkand and Ashinda. Mirza Qalich Beg recorded its pronunciation (Khanda) in the English translation of Chach Nama and in the Christian history it is written as Iskander (which is the Persian and Arabic form of Alexander). The famous traveler Ibn Battuta, who reached Uch in the eighth century AH, in 734 AH, he writes that we walked from Bhakkar and reached the city of Uch. This city is situated on the banks of the Indus River and is a large city. Its markets are very good and its buildings are beautiful and strong. . And different people came to this land, Alexander the Great, Kingham Panchmech, Mahmud Ghaznavi, Hassan Arghun Sindhi, and it is called the land of various historical buildings, mosques, shrines, palaces, saints.